Incorporating the latest pediatric nutrition support guidelines into clinical practice. Issue 2 (February 2019) - Irving, Sharon Y.; Guenter, Peggi; Mehta, Nilesh M.
Abstract : Abstract: Optimal nutrition support in critically ill children is associated with improved outcomes and decreased mortality. Nutrition provision often competes with other care priorities in critically ill patients. The 2017 Guidelines for the Provision and Assessment of Nutrition Support Therapy in the Pediatric Critically Ill Patient supplement clinician knowledge and inform best practices for nutrition therapy in this vulnerable patient population. Abstract : Learn how the 2017 Guidelines supplement clinician knowledge and inform best practices for nutrition therapy in critically ill children.